Proximate analysis and formulation of weaning food using germinated cereals, pulses and ground nut (Asian-Australasian Journal of Food Safety and Security, 2021)
A combination of nutritionally inferior diets and improper feeding practices are major contributing factors to the development of childhood malnutrition. Complementary feeding improvement should be of highest priority for nutrition of infant and young children containing all essential nutrients at required amount. The objective of this study was designed to investigate the inclusion of weaning food formulation and evaluating compositional and functional properties of the products. The analysis undertaken in this study was infant food formulation, proximate composition, mineral concentration and sensory properties. The moisture content in this study ranged from 1.49 ± 0.12 to 3.89 ±0.12, crude protein from 15.09 ± 0.05 to 16.79± 0.01, crude fat from 11.11 ± 0.07 to 12.80 ± 0.00, total ash from 2.06 ± 0.03 to 2.21 ± 0.00, carbohydrate from 65.9740 ± 0.24 to 68.2641 ± 0.14 and energy value ranged from 431.68 ± 0.05 to 449.18 ± 0.57. From the result provided, sample-A contained the highest protein, moisture, fat content than sample-B. But carbohydrate and energy are highest in sample-B than sample-A. The two macro minerals mg/100 g of Ca and Zn in the study were ranged from lower 0.60±0.07 to 0.79±0.01 and 1.05±0.01 to 2.44±0.06 respectively. Beta-carotene is varied from 0.90±o.01 to 1.17±0.00. Sensory parameters such as colour, appearance, texture, taste, aroma and overall acceptability is high in sample-A than to sample-B. Finally, from the general trend observed in this study that both the weaning foods prepared from cereal, legume, pulse flour provided better nutritional and functional compositions to meet nutrient dense of infant foods.Asian Australas. J. Food Saf. Secur. 2021, 5 (2), 32-42